Selected meteorological phenomena posing a hazard to aviation: a case study on Bydgoszcz airport, central Poland - Araźny, Andrzej; Łaszyca, Edward (Bulletin of Geography. Physical Geography Series, 2020)
The article describes the occurrence of selected weather phenomena that are hazardous to aviation (thunderstorms, hail, fog and glaze) in Bydgoszcz. The work employs 1971–2010 data from the Bydgoszcz-Airport meteorological station. The hazardous atmospheric phenomena selected for analysis hinder or sometimes even prevent aviation. Of the analysed weather phenomena in Bydgoszcz, those most hazardous to aviation are fog and thunderstorms. The average annual numbers of days featuring them exceed 71 and 14, respectively. The analysis shows that statistically significant threats to aviation have decreased, e.g. number of days with fog (by 4.76 days/10 yrs) and days with thunderstorms (by 1.68 days/10 yrs). However, no clear trends can be seen for the number of days with hail (decrease of 0.14 days/10 yrs) and days with glaze (an increase of 0.16 days/10 yrs).